Antibacterial activity against Lactobacillus acidophilus and Streptococcus mutans from endophytic mold of binahong leaf (Anredera cordifolia (Ten.) Steenis) - Permanasari, Etin Diah; Roinaldo, Roinaldo (Universitas Merdeka Pasuruan, 2025)
Endophytic microbe is usually used as a natural source to explore novel metabolites which has therapeutic activities. This research’s aim is to determine the antibacterial activity of endophytic molds which grow in the tissue of binahong leaf (Anredera cordifolia (Ten.) Steenis) to resist Lactobacillus acidophilus and Streptococcus mutans. Four endophytic mold isolates were obtained, which were KTS1, KTS2, KTS3, and KTS4. The screening of antibacterial activities for L. acidophilus and S. mutans was carried out from the supernatant of each isolate, and the highest inhibition was obtained by KTS1 with the inhibition diameter of 2,82 mm for L. acidophilus and 2,89 mm for S. mutans. The grading extraction with n-hexane, ethyl acetate, and methanol was used to extract the supernatant. The microdilution method was used to determine the antibacterial activity by measuring the absorbances with a microplate reader at a 595 nm of wavelength. The respective of IC50 of KTS1 in the ethyl acetate (KTS1EA) and methanol (KTS1ME) against L. acidophilus were 9007,80 µg/ml and 10119,45 µg/ml. The relative potency of KTS1EA and KTS1ME to erythromycin against L. acidophilus were 0,0023 and 0,0020 times as respectively. The respective of relative potency of KTS1EA and KTS1ME to erythromycin against S. mutans were 0,0032 and 0,0021 times. However, the IC50 of KTS1EA and KTS1ME against S. mutans were 5878,03 µg/ml and 8928,75 µg/ml as respectively.